2003
DOI: 10.1088/0022-3727/36/15/201
|View full text |Cite
|
Sign up to set email alerts
|

The physics of soft x-ray lasers pumped by electron collisions in laser plasmas

Abstract: Soft x-ray lasers in the 3.5-50 nm wavelength range have been developed in many laboratories. The shortest wavelengths and highest output irradiances have been produced using plasmas created by optical lasers as the lasing medium. The optical laser is focused into a line on a solid target and the x-ray laser action occurs by amplification along the line with sufficiently high gain that mirrors are not needed. Population inversions are produced by free-electron collisions exciting bound electrons into metastabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 138 publications
0
49
0
Order By: Relevance
“…Saturated x-ray lasing at wavelengths in the range 5.9 -30 nm [1,2] and with pulse durations down to ≈ 3 ps [3,4] has been produced in plasmas pumped by optical lasers. In these experiments, a first laser pulse incident onto a solid in a line focus creates a pre-formed plasma of Ne-or Ni-like ionization and a second pulse heats free electrons that produce population inversions by monopole electron collisional excitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saturated x-ray lasing at wavelengths in the range 5.9 -30 nm [1,2] and with pulse durations down to ≈ 3 ps [3,4] has been produced in plasmas pumped by optical lasers. In these experiments, a first laser pulse incident onto a solid in a line focus creates a pre-formed plasma of Ne-or Ni-like ionization and a second pulse heats free electrons that produce population inversions by monopole electron collisional excitation.…”
Section: Introductionmentioning
confidence: 99%
“…In these experiments, a first laser pulse incident onto a solid in a line focus creates a pre-formed plasma of Ne-or Ni-like ionization and a second pulse heats free electrons that produce population inversions by monopole electron collisional excitation. Lasing occurs in Ne-or Ni-like ions between 3p -3s and 4d -4p levels respectively as the upper levels are metastable to decay to the ground 2p and 3d states respectively [1,2]. It has been shown that this mechanism of pumping x-ray lasers works with pumping laser pulses of duration from ≈ 100 ps down to < 1 ps, but that gain is always present for times 10 ps with minimum observed x-ray lasing duration of 3 ps [3].…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of 1400 eV corresponds to the energy of the laser after absorption in the interaction volume of 25 |im x 40 |im x 6 mm with 50% losses. Tallents [41 ] assumes 30% of the energy of the laser beam is lost to nonlinear effects and we assume that radiative losses may also limit the energy of the electrons. This seems consistent with temperatures found in other simulations conducted on Molybdenum and Palladium with an appropriate GRIP absorption [39].…”
Section: Fast Ionisation Model Alonementioning
confidence: 99%
“…Interestingly, full raytracing does predict two peaks of Intensity scales shown are arbitrary above the image intensifier and streak camera noise set at approximately zero level. Model fit for peak small signal gain of (a) 23 cm or (b) 60 cm , a gain duration of (a) 22 ps or (b) 35 ps and the ratio of spontaneous emission to the saturation irradiance R = 10 (see [16]) is shown (as labeled). Fit obtained from three-dimensional ray traces [22] of the X-ray laser output is also superimposed (as labeled).…”
Section: Measurements Of Short Wavelength Pulse Durationmentioning
confidence: 99%
“…Recent reviews on X-ray lasers should be referred to for more general information on the physics of X-ray lasers [16] or for reviews of different approaches to plasma-based X-ray lasing [17]- [19]. In this paper, recent experimental work on the development of X-ray lasers undertaken using the VULCAN laser at the Rutherford Appleton Laboratory is compared to detailed simulations.…”
mentioning
confidence: 99%